Collagen‐induced arthritis as an animal model of rheumatoid cachexia. Issue 3 (25th March 2018) - Alabarse, Paulo V.G.; Lora, Priscila S.; Silva, Jordana M.S.; Santo, Rafaela C.E.; Freitas, Eduarda C.; de Oliveira, Mayara S.; Almeida, Andrelise S.; Immig, Mônica; Teixeira, Vivian O.N.; Filippin, Lidiane I.; Xavier, Ricardo M.
Abstract: Background: Rheumatoid arthritis is characterized by chronic polyarticular synovitis and presents systemic changes that impact quality of life, such as impaired muscle function, seen in up to 66% of the patients. This can progress to severely debilitating state known as rheumatoid cachexia—without loss of fat mass and body weight—for which there is little consensus in terms of diagnosis or treatment. This study aims to evaluate whether the collagen‐induced arthritis (CIA) animal model also develops clinical and functional features characteristic of rheumatoid cachexia. Methods: Male DBA1/J mice were randomly divided into 2 groups: healthy animals (CO, n = 11) and CIA animals ( n = 13). The clinical score and edema size, animal weight and food intake, free exploratory locomotion, grip strength, and endurance exercise performance were tested 0, 18, 35, 45, 55, and 65 days after disease induction. After euthanasia, several organs, visceral and brown fat, and muscles were dissected and weighed. Muscles were used to assess myofiber diameter. Ankle joint was used to assess arthritis severity by histological score. Statistical analysis were performed using one‐way and two‐way analyses of variance followed by Tukey's and Bonferroni's test or t ‐test of Pearson and statistical difference were assumed for a P value under 0.05. Results: The CIA had significantly higher arthritis scores and larger hind paw edema volumes than CO. The CIA had decreased endurance exercise performance total time (fatigue; 23, 22, 24, and 21% at 35, 45, 55, and 65 days, respectively), grip strength (27, 55, 63, 60, and 66% at 25, 35, 45, 55, and 65 days, respectively), free locomotion (43, 57, 59, and 66% at 35, 45, 55, and 65 days, respectively), and tibialis anterior and gastrocnemius muscle weight (25 and 24%, respectively) compared with CO. Sarcoplasmic ratios were also reduced in CIA (TA: 23 and GA: 22% less sarcoplasmic ratio), confirming the atrophy of skeletal muscle mass in these animals than in CO. Myofiber diameter was also reduced 45% in TA and 41% in GA in CIA when compared with the CO. Visceral and brown fat were lighter in CIA (54 and 39%, respectively) than CO group. Conclusions: The CIA model is a valid experimental model for rheumatoid cachexia given that the clinical changes observed were similar to those described in patients with rheumatoid arthritis.